DIPLOMATIC PROTOCOL AS A POLITICAL TOOL OF MODERN INTERNATIONAL RELATIONS - Zelinska , O.M. (The actual problems of regional economy development, 2023)
Today, diplomacy is an important component of the process of formation of states. Under the influence of certain factors, it changed, but it was always aimed at protecting the national interests of states. The formation of diplomacy as a special type of state activity took place at the turn of the 16th and 17th centuries, when the first permanent diplomatic missions appeared at the courts of monarchs, and later - special departments that dealt with correspondence between sovereigns, reception of foreign delegations, and negotiations. However, historical experience shows that to ensure the effective implementation of diplomatic relations in their entirety, the use of international legal norms alone is not sufficient. It is also important to observe certain traditions, rules, conventions, customs, that is, what is called diplomatic protocol. Thus, the correct observance of the rules and norms of the diplomatic protocol can contribute to the improvement of bilateral relations and the effective resolution of various issues between the two parties. In the event of intentional or unintentional violation of such norms, it may, on the contrary, complicate the relations between the two states, or cause damage to their prestige and image. Also, through the use of diplomatic protocol tools, representatives of diplomatic missions can carefully and elegantly demonstrate their own attitude towards certain subjects of international relations or issues of world politics. Studies of issues related to the use of diplomatic protocol norms in the conditions of globalization of the world economy are covered in the scientific works of both domestic and foreign scientists. The value of scientific works with their theoretical and practical studies is quite high, but issues related to the effectiveness of the application of diplomatic protocol tools require further consideration. The object of the research is the diplomatic protocol. The subject of the study is the practice of using the tools of the diplomatic protocol in world politics. The purpose of the article is to reveal the content and specifics of the mechanism of international legal functioning of the diplomatic protocol, taking into account the realities of the modern world. The main research methods used in the research were generally philosophical, dialectical, logical-semantic, synthesis method, systemic-structural, sociological, and statistical method. The most important value belongs to the philosophical method in general, because the study of the formation of negotiating tendencies with the application of diplomatic norms has its roots reaching a depth that is expedient to investigate with the help of philosophical reasoning. The use of the dialectical method of cognition is due to the opportunity to investigate the problems of the interaction of diplomats in the unity of economic, social, moral and legal content. The synthesis method provides an opportunity to supplement the categorical apparatus with new definitions. The results of the research were the conclusions made on the basis of the study of the political instruments of the diplomatic protocol and their influence on the further negotiating positions of the states. The practical significance of the scientific research and its results is the study of the consequences of observing or ignoring the diplomatic protocol (consciously or unconsciously) on the activities of the subjects involved in the negotiation process.